To Resolve or Not To Resolve, that Is the Question: The Dual-Path Model of Incongruity Resolution and Absurd Verbal Humor by fMRI - Dai, Ru H.; Chen, Hsueh-Chih; Chan, Yu C.; Wu, Ching-Lin; Li, Ping; Cho, Shu L.; Hu, Jon-Fan (Frontiers in Psychology, 2017)
It is well accepted that the humor comprehension process involves incongruity detection and resolution, which then induces a feeling of amusement. However, this three-stage theory does not apply to absurd humor (so-called nonsense humor). Absurd humor contains an unresolvable incongruity but can still induce a feeling of mirth. In this study, we used functional magnetic resonance imaging (fMRI) to identify the neural mechanisms of absurd humor comprehension and appreciation. Specifically, to investigate the neural substrates associated with the complete resolution of incongruity resolution humor and partial resolution of absurd humor. Based on the fMRI data, we propose a dual-path model of incongruity resolution and absurd verbal humor. According to this model, the detection and resolution for the incongruity of incongruity resolution humor activates brain regions involved in the temporo-parietal lobe (TPJ and IPL) implicated in the integration of multiple information and precuneus, likely to be involved in the ability of perspective taking. The appreciation of incongruity resolution humor activates regions the posterior cingulate gyrus, implicated in autobiographic or event memory retrieval, and parahippocampal gyrus (PHG), implying the pleasure feelings. By contrast, the partial resolution of absurd humor elicits greater activation in the fusiform gyrus, that have been implicated in word processing, the inferior frontal gyrus (IFG) for the process of incongruity resolution and superior temporal gyrus (STG) for the function of pragmatic awareness.